2009
DOI: 10.1021/ja9033445
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Iridium(IV) by Monoanionic Dialkyldiarylguanidinato Ligands

Abstract: Electron-rich tris(guanidinato) complexes of Ir(III), [Ir{ArNC(NR(2))NAr}(3)] (where R = Me or Et; Ar = Ph or 4-MeC(6)H(4)), were synthesized from the respective [Ir{ArNC(NR(2))NAr}(C(8)H(14))(2)] precursors (C(8)H(14) = cis-cyclooctene), are air-sensitive, and can be electrochemically oxidized in two one-electron transfer steps. The first electron transfer is reversible and occurs at much lower potentials than typical for Ir(III). Chemical oxidation by [FeCp(2)]PF(6) afforded isolable, paramagnetic Ir(IV) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The Δ E 1/2 of the first redox step is much lower than those observed in typical iridium­(III) complexes. It is, however, comparable to Rhode’s dialkyldiarylguanidinatoiridium­(III) complexes ([Ir­{ArNC­(NR 2 )­NAr} 3 ]; Δ E 1/2 = −0.27 to −0.41 V vs Fc/Fc + ) and Crabtree’s mononuclear pyridine–alkoxide iridium­(III) system (Δ E 1/2 = −0.18 to −0.69 V vs Fc/Fc + ), both of which could be oxidized to afford isolable iridium­(IV) and/or iridium­(V) complexes. The facile oxidation of 4 is likely due to conjugation between the metal d orbitals with the π-rich dpa Ar2 NHC CCC-pincer ligand.…”
Section: Resultsmentioning
confidence: 76%
“…The Δ E 1/2 of the first redox step is much lower than those observed in typical iridium­(III) complexes. It is, however, comparable to Rhode’s dialkyldiarylguanidinatoiridium­(III) complexes ([Ir­{ArNC­(NR 2 )­NAr} 3 ]; Δ E 1/2 = −0.27 to −0.41 V vs Fc/Fc + ) and Crabtree’s mononuclear pyridine–alkoxide iridium­(III) system (Δ E 1/2 = −0.18 to −0.69 V vs Fc/Fc + ), both of which could be oxidized to afford isolable iridium­(IV) and/or iridium­(V) complexes. The facile oxidation of 4 is likely due to conjugation between the metal d orbitals with the π-rich dpa Ar2 NHC CCC-pincer ligand.…”
Section: Resultsmentioning
confidence: 76%
“…[10] In contrast, both 1 IV and 2 IV have approximately 0.7 unpaired electrons per Ir and give rhombic EPR signals similar to those of other Ir IV monomers ( Figure S6). [7,11] Thed iamagnetism of 1 V and 2 V indicates an S = 0d 4 Ir V . Prior work showed that having strong donor alkoxides in the same coordination plane favors Ir III to Ir IV oxidation in aseries of Ir(pyalk) 3 and Ir(pyalk) 2 Cl 2 monomers.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Because of its biological interest, guanidine has been used as a ligand for the synthesis of a number of metal complexes; however, little or no reactivity of these complexes has been reported. We recently reported the synthesis of novel osmium­(III) guanidine, mer -[Os­{N­(H)­C­(NH 2 ) 2 }­( L ) (CN) 3 ] − ( OsG , HL = 2-(2-hydroxyphenyl)­benzoxazole) and N -hydroxyguanidine ( mer -[Os­{NHC­(NH 2 ) (NHOH)}­( L ) (CN) 3 ] − , γ -OsGOH ) complexes via the nucleophilic addition of NH 3 and NH 2 OH, respectively, at an osmium­(III) hydrogen cyanamide precursor ([Os­(NHCN)­( L ) (CN) 3 ] 2– , OsNHCN ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%